More than A1C: Types of success among adults with type-2 diabetes participating in a technology-enabled nurse coaching intervention. Issue 1 (January 2019) - Fazio, Sarina; Edwards, Jennifer; Miyamoto, Sheridan; Henderson, Stuart; Dharmar, Madan; Young, Heather M.
Highlights: A person-centered approach measures success in diabetes control in relation to individual goals. Broader definition of success includes making positive personal changes to manage diabetes. Nurse coaching and technology support goal setting, health tracking and resolving barriers. Success types: change in behavior, mindset, engagement, physical/emotional health, indicators. Abstract: Objective: Success in diabetes research and self-management is often defined as a significant decrease in glycated hemoglobin (A1C). The aim of this article is to explore different types of successes experienced by adults with type-2 diabetes participating in a health technology and nurse coaching clinical trial. Methods: A qualitative analysis was conducted using surveys and documentation from motivational interview-based coaching sessions between study nurses and intervention participants. Results: Of the 132 cases reviewed, types of success predominantly fell into five categories: 1) change in health behaviors ; 2) change in mindset or awareness ; 3) change in engagement with healthcare resources ; 4) change in physical or emotional health ; and 5) change in health indicators . Conclusion: Experiences of success in diabetes are more varied than traditional A1C-based outcome models. Our findings suggest coaching and technology can assist patients to achieve a range of successes in diabetes management through goal setting, health tracking, resolving barriers, and aligning goals with factors that impact change. Practice implications: While A1C reduction is a critical factor in decreasing risk of diabetes-related complications, when healthcare professionals focus on A1C as the main indicator of diabetes management success, important changes in individuals' health and well-being may be overlooked or undervalued.